GAGASAN RESTORATIVE JUSTICE SEBAGAI PENYELESAIAN TINDAK PIDANA KORUPSI: STUDI ANALISIS MAQÂṢID AL-SYARÎAH - Fira Mubayyinah (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2022)
This research begins with a discourse of thought that is currently being debated in the community, which is related to law enforcement in eradicating corruption with state financial losses under fifty million rupiah. Some people still have the belief that eradicating corruption must be carried out with repressive means and the imposition of the maximum amount of punishment. Others are concerned that the Restorative Justice approach in eradicating corruption is mitigating and not causing a deterrent effect for potential perpetrators. This discourse began to be widely discussed after the Attorney General, Burhanudin, publicly stated that the steps in law enforcement at the Prosecutor's Office in dealing with corruption cases with a state financial loss of less than fifty million rupiah should be resolved using a Restorative Justice approach. This research is focused on how Restoractive Justice is used as an approach to solving corruption cases with state financial losses under fifty million rupiah in the perspective of Maqâshid al-syarî'ah. The research method used is juridical-normative, with a statutory and conceptual approach. The results of the study indicate that the settlement of corruption cases with a Restorative Justice approach is in accordance with Maqâshid al-syarî'ah.